The Role of Knowledge-Oriented Leadership in Enhancing Employee Retention Through Human Resource Development: A Qualitative Case Study at Mega Baja Indonesia Zone 16 - Laura Ahda Tania; Editya Nurdiana (Greenation International Journal of Economics and Accounting, 2025)
This research aims to analyze the role of knowledge-based leadership in strengthening employee retention through human resource (HR) development practices in manufacturing organizations. The research used a qualitative approach with a case study design carried out at Mega Baja Indonesia Zone 16. Data collection was carried out through in-depth interviews, direct observation and analysis of organizational documents, which were then analyzed using thematic analysis techniques to identify patterns and relationships between research variables. The research results show that knowledge-based leadership plays an important role in encouraging work learning, continuous mentoring, and open information that is integrated with career development systems and increasing employee competency. These practices shape perceptions of organizational support and professional growth opportunities, which significantly strengthen employees' engagement and commitment to staying with the organization. These findings confirm that the influence of knowledge-based leadership on employee retention occurs through a systematic HR development mechanism. This research provides theoretical contributions by expanding understanding of the role of knowledge-based leadership in supporting talent sustainability, as well as practical contributions for manufacturing organizations in designing HR development strategies oriented towards employee retention.